Analisis Putusan Bebas terhadap Tindak Pidana Pemeliharaan Satwa yang Dilindungi (Studi Putusan Nomor 809/Pid.Sus/2024/Pn Dps) - Pratama, M. Ilham Wira (Universitas Muhammadiyah Yogyakarta, 2025)
The Panel of Judges at the Denpasar District Court through Decision Number 809/Pid.Sus/2024/Pn Dps issued a verdict of acquittal from all charges (vrijspraak) against the defendant who was charged with Article 21 paragraph (2) letter a in conjunction with Article 40 paragraph (2) of the KSDA-HE Law for the possession of four Javan Porcupines (Hystrix Javanica) which are protected animals, due to the failure to fulfill the element of